Marine n-3 PUFAs modulate IKs gating, channel expression, and location in membrane microdomains. (11th December 2014) - Moreno, Cristina; de la Cruz, Alicia; Oliveras, Anna; Kharche, Sanjay R.; Guizy, Miriam; Comes, Nùria; Starý, Tomáš; Ronchi, Carlotta; Rocchetti, Marcella; Baró, Isabelle; Loussouarn, Gildas; Zaza, Antonio; et al.
Abstract: Aims: Polyunsaturated fatty n-3 acids (PUFAs) have been reported to exhibit antiarrhythmic properties. However, the mechanisms of action remain unclear. We studied the electrophysiological effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on I Ks, and on the expression and location of Kv 7.1 and KCNE1. Methods and results: Experiments were performed using patch-clamp, western blot, and sucrose gradient techniques in COS7 cells transfected with Kv 7.1/KCNE1 channels. Acute perfusion with both PUFAs increased Kv 7.1/KCNE1 current, this effect being greater for DHA than for EPA. Similar results were found in guinea pig cardiomyocytes. Acute perfusion of either PUFA slowed the activation kinetics and EPA shifted the activation curve to the left. Conversely, chronic EPA did not modify Kv 7.1/KCNE1 current magnitude and shifted the activation curve to the right. Chronic PUFAs decreased the expression of Kv 7.1, but not of KCNE1, and induced spatial redistribution of Kv 7.1 over the cell membrane. Cholesterol depletion with methyl-β-cyclodextrin increased Kv 7.1/KCNE1 current magnitude. Under these conditions, acute EPA produced similar effects than those induced in non-cholesterol-depleted cells. A ventricular action potential computational model suggested antiarrhythmic efficacy of acute PUFA application under I Kr block. Conclusions: We provide evidence that acute application of PUFAs increases Kv 7.1/KCNE1 through a probably direct effect, and shows antiarrhythmic efficacy under I Kr block. Conversely, chronic EPA application modifies the channel activity through a change in the Kv 7.1/KCNE1 voltage-dependence, correlated with a redistribution of Kv 7.1 over the cell membrane. This loss of function may be pro-arrhythmic. This shed light on the controversial effects of PUFAs regarding arrhythmias.